An increasement of general occupational safety level at food industry plants - Evtushenko, Olga (My University, 2014)
A purpose of research is to increase the occupational safety level through elaboration of general injury risk model at food processing.
Keywords: risk; forecast; safety; work; accident; ризик; безпека; прогноз; робота; аварія; работа; кафедра екології та екоменеджменту